(E)-N′-(5-Chloro-2-hydroxybenzylidene)-p-toluenesulfonohydrazide - Kia, Reza (International Union of Crystallography, 2008)
The title compound, C(14)H(13)ClN(2)O(3)S, features an intramolecular O—H⋯N hydrogen bond which generates an S(6) ring motif. Intermolecular N—H⋯O hydrogen bonds and C—H⋯O close contacts link neighbouring molecules forming R (2) (2)(13) ring motifs. In the crystal structure, molecules are further linked by C—H⋯Cl interactions, forming one-dimensional extended chains along the c axis. The dihedral angle between the two benzene rings is 86.06 (3)°. The crystal structure is further stabilized by weak intermolecular π–π interactions [interplanar stacking distance = 3.357 (7) Å].